Heart failure in a neonate with multiple cardiac masses. Issue 1 (21st September 2016) - Nasr, Emad; Ibrahim, Michael; Yacoub, Magdi
Abstract : Clinical introduction: A 16-day-old male neonate weighing 3.4 kg presented with severe heart failure. His heart rate was 190/min, normal sinus rhythm, blood pressure was 55/30 mm Hg and respiratory rate was 65/min. Transthoracic echocardiography and cardiac MRI showed multiple intracardiac masses; the largest was filling most of the left ventricular cavity (figure 1 A) (see online supplementary video 1 and figure S1 ), measuring around 2.8 cm×1.8 cm and arising from the apical septum. Left ventricular function was moderately impaired with an ejection fraction of 40%. Due to accelerated haemodynamic instability, the mass was excised surgically. Through left ventriculotomy, a large mass could be identified which was attached with a pedicle to the apical septum. This mass was excised with its pedicle. During early postoperative course, the patient developed subdural and intraventricular haemorrhage, necessitating insertion of a ventriculoperitoneal shunt. MRI of the brain showed dark-signalled subependymal nodules and multiple cortical patches of high T2 signals (see online supplementary figure S2). The patient had no neurological sequelae and was discharged home. The patient was discharged home with no neurological sequelae. During the 2-year follow-up period, serial echocardiograms showed regression of the rest of the cardiac tumours and improvement of cardiac functions (see online supplementary figure S3). However, fibrous plaques were observed on the child's forehead. Question: What is the most likely diagnosis? Hibernoma Fibroma Rhabdomyoma Rhabdomyosarcoma